Assessing the cost of Iran deposit insurance (Iran) - hossein amiri (مدلسازی اقتصادسنجی, 2017)
Considering the role and importance of the banking system in the economic growth and development of countries, attention to the stability of the banking system has an undeniable role in economic stability. For this purpose, the deposit insurance system plays a major role. This article uses Merton’s deposit insurance pricing model to analyze the cost of Iran deposit insurance. For this purpose, 9 private banks were selected during the period of 2010-2015. In order to choose the type of deposit, five-year deposits are used as the longest bank deposits in terms of maturity. A market-value-based maximum likelihood estimation method developed by Duan is employed to compute the inputs needed for Merton’s formula. Given that in the Merton method, the asset value of a bank and the standard deviation of return on assets are unknown, Therefore, in the Ron and Verma method, based on the stock value and its volatility, and in the MLE method, it is calculated based on the maximum likelihood function. Considering the high rate of deposit insurance according to the results, it is observed that the risk of banking in Iran is increasing. Also, by comparing the estimates obtained using Ron and Verma method and the maximum likelihood method, the deposit insurance rate is higher based on the MLE method, which is an effective method for calculating the deposit insurance rate.